RANCANG BANGUN FUEL FLOW METER UNTUK MENGUKUR KONSUMSI BAHAN BAKAR MESIN SEPEDA MOTOR EMPAT LANGKAH - Yelma Dianastiti; Anggara Ardiyanta; Wahyu Cahyadi; Warju Warju; Muhammad Pratama (Otopro, 2022)
In general, in knowing the fuel consumption of a motorcycle, motorcycle owners do this by looking at the fuel indicator on the instrument panel marked "F" meaning full, and "E" emergency. However, in the context of learning, these conditions make it difficult for students to read how much vehicle fuel consumption is viewed at each engine rotation (RPM). Referring to these conditions, the need for a fuel consumption meter is absolute. Therefore, the main objective of this research is to produce a fuel flow meter that can function properly to measure motorcycle fuel consumption so that it can be used as a support for gasoline motorbike technology lectures at the Automotive Technology Vocational Education Study Program) Universitas Bhinneka PGRI. This type of research is experimental research. The research object is the 2005 Honda Supra Fit. The standard for measuring fuel consumption is based on SNI 7554:2010 standards. Data analysis used a quantitative descriptive method. Research equipment and instruments used are a fuel meter, stopwatch, tachometer, and blower. The results of this study indicate that the fuel flow meter functions well in measuring fuel consumption. When calculated, from idle to high speed, there is an average increase in fuel consumption of 0.11 liters/hour or 41% at every RPM. This shows that the fuel flow meter can be used as a support for gasoline engine technology lectures.